BRANDING UNIVERSITAS KRISTEN INDONESIA MALUKU (UKIM) SEBAGAI KAMPUS ORANG BASUDARA - Tahitu, Amelia; Wattimena, Demsy; Batlolona, Jannyfer Brigitte (JURNAL BADATI, 2025)
Quantitative research can be interpreted as a method used to research a certain population or sample, sampling techniques are generally carried out randomly, data collection uses research instruments, therefore the method used in this research is to obtain data from certain natural (not artificial) places, but researchers carry out treatments in collecting data, by distributing questionnaires, structured interviews and so on. Based on the results of research with 35 respondents' answers to questions, and researchers obtained results using descriptive quantitative analysis, to determine the percentage trends of the indicators being measured. So the research results obtained are as follows; 1). Tolerance and pluralism on the UKIM campus is reflected in the acceptance of various religious and cultural backgrounds, both among students and teaching staff. The research results found that the achievement of tolerance and pluralism was quite high, with 23 respondents or 66% agreeing with tolerance and pluralism in UKIM, while 12 respondents or 34% felt that the implementation of these values was not fully optimal. 2). University Inclusivity, shows that as many as 23 respondents or 66% feel that inclusivity at UKIM, as a Basudara People's Campus, has played a role in strengthening the campus' image as a Basudara campus that is open and accepting of differences, while 12 respondents or 34% feel that there is room for improvement in creating a more inclusive campus community in the future. 3). UKIM's image, as a campus that supports education without discrimination, has succeeded in strengthening its branding as a Basudara People's Campus, where everyone is treated equally and respected regardless of differences. The research results found that 28 respondents or 79% supported education without discrimination at UKIM, and were considered successful in fostering and encouraging a conducive academic atmosphere among the campus community, including the teaching and learning process, campus facilities and extracurricular activities. 4). As a campus that has the brand "Kampus Orang Basudara" and is better known for its pluralism, UKIM has utilized the richness of local and national culture as part of its branding strategy for the Orang Basudara Campus, and 7 respondents or 21% stated that it needed to improve anti-discrimination equality policies. The research results found that 27 respondents or 77% stated that cultural diversity was an important part of UKIM's identity. This shows that the values of the Basudara people, which emphasize togetherness in diversity, have been implemented well in campus life, and as many as 8 respondents or 23% felt that aspects of cultural diversity were not fully optimal. And UKIM has succeeded in building a reputation as a campus that promotes the values of togetherness, difference and equality which are in line with the concept of "Basudara People".